2013
DOI: 10.3389/fcimb.2013.00013
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine delivery using nanoparticles

Abstract: Vaccination has had a major impact on the control of infectious diseases. However, there are still many infectious diseases for which the development of an effective vaccine has been elusive. In many cases the failure to devise vaccines is a consequence of the inability of vaccine candidates to evoke appropriate immune responses. This is especially true where cellular immunity is required for protective immunity and this problem is compounded by the move toward devising sub-unit vaccines. Over the past decade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
344
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(347 citation statements)
references
References 172 publications
(165 reference statements)
2
344
1
Order By: Relevance
“…Furthermore, polymer selection can influence intrinsic adjuvant effects, biocompatibility and biodegradability. The most widely studied particles so far are those produced from poly(α-hydroxyl acids), poly(amino acids) and polysaccharides with the most common polymers being poly(lacticco-glycolic acid) (PLGA), poly(lactic acid) (PLA), β-glucans, alginate and chitosan [186][187][188]. While biodegradable particles have been extensively investigated for vaccine delivery, the potential of nonbiodegradable alternatives such as carbon, silica and gold has also been suggested.…”
Section: Synthetic Particle-based Strategiesmentioning
confidence: 99%
“…Furthermore, polymer selection can influence intrinsic adjuvant effects, biocompatibility and biodegradability. The most widely studied particles so far are those produced from poly(α-hydroxyl acids), poly(amino acids) and polysaccharides with the most common polymers being poly(lacticco-glycolic acid) (PLGA), poly(lactic acid) (PLA), β-glucans, alginate and chitosan [186][187][188]. While biodegradable particles have been extensively investigated for vaccine delivery, the potential of nonbiodegradable alternatives such as carbon, silica and gold has also been suggested.…”
Section: Synthetic Particle-based Strategiesmentioning
confidence: 99%
“…DNA administration, which exploits host cellular processes for antigen expression,78, 79, 80 is the simplest approach that may be feasible. In addition to administration of naked DNA with electroporation, several biotechnology alternatives exist as DNA vaccine delivery methods, and new technologies continue to offer promise 81, 82, 83, 84. Another unresolved question is how best to deliver such a complex set of antigens.…”
Section: Immune Selection In Longitudinal Samples: Ontogeny Of Cd4bsmentioning
confidence: 99%
“…31 For example, certain cationic lipids such as the DOTAP used to prepare liposomes are immunostimulatory. 32 It was shown that treatment of DCs with these cationic liposomes induced both CD80/CD86 expression on DCs surface and the release of proinflammatory cytokines such as TNF-a by DCs. 32 However, the adjuvant activity of NPs is depended on the physicochemical properties (e.g.…”
Section: Important Characteristics Of Nanoparticle-based Vaccine Delimentioning
confidence: 99%
“…32 It was shown that treatment of DCs with these cationic liposomes induced both CD80/CD86 expression on DCs surface and the release of proinflammatory cytokines such as TNF-a by DCs. 32 However, the adjuvant activity of NPs is depended on the physicochemical properties (e.g. the material's composition, particle size, surface charge, production methods, and additional surface modifications) and should be explored further.…”
Section: Important Characteristics Of Nanoparticle-based Vaccine Delimentioning
confidence: 99%